Phantom Rhetorics: From Pathos to Affect - (:unkn) unknown (My University, 2014)
Despite much interest in scholarship on affect and emotion in the field of rhetoric and composition in the last several decades, scholars have not yet used this scholarship to revise or extend rhetorical understandings of pathos. In our field, pathos is still primarily conceived as a linguistic tool and is rarely theorized as more than a rhetorical appeal. This conception of pathos overlooks the varied roles of emotions in rhetorical situations (e.g., how embodied or mediated emotions persuade). I argue that extending studies of pathos to include affect theory reveals more complicated rhetorical functions of pathos. But rather than treat "affect" and "emotion" as separate concepts and phenomena (like many scholars in our field), I argue it is the relationship between affect and emotion that ought to be better theorized to complicate current understandings of pathos. After close analysis of how affect and emotion have been studied in our field, I put forth a theoretical framework for rhetorical study of affects and emotions which 1) approaches rhetoric ontologically, 2) reconnects affect to assemblage theory, and 3) defines bodies (human and nonhuman) via their capacity to affect and be affected. I apply this framework to a case study of an outbreak of mass psychogenic illness (previously called "mass hysteria") among a group of mostly high school girls in LeRoy, NY in 2011. I begin my analysis of this case by looking for the affects and emotions at its center. Looking for pathos beyond the texts and discourses surrounding the case, this project examines the rhetoricity of bodies, bodily processes, assemblages, and media. This project seeks to broaden current understandings of pathos, to illustrate what it might look like to study pathos as the core of rhetorical studies.